High [Formula Omitted]-Factor In-Plane-Mode Resonant Microsensor Platform for Gaseous/Liquid Environment - Seo, Jae Hyeong; Brand, O (Journal of microelectromechanical systems, 2008)
This paper presents a novel resonant-microsensor platform for chemical and biological sensing applications in gaseous and liquid environment. The disk-shape microstructure is operated in a rotational in-plane mode with typical resonance frequencies between 300 and 1000 kHz. By shearing the surrounding fluid instead of compressing it, damping is reduced, and high quality factors are achieved. The resonators feature electrothermal excitation elements and a piezoresistive Wheatstone bridge for detection, sensitive only to the in-plane rotational vibration mode. Microresonators with different dimensions have been fabricated and extensively characterized, achieving quality factors of up to 5800 in air. First tests performed in water after parylene coating show a Q factor of approximately 100. Short-term frequency stabilities obtained from Allan-variance measurements with 1-s gate time are as low as 1.2times10 super(-8) in air and 2.3times10 super(-6) in water. An analytical model describing the mechanical behavior of the disk resonators, represented by a simple harmonic oscillator, is derived. In particular, expression for the resonance frequency and quality factor of the disk resonators subject to air/liquid damping are proposed and compared with experimental results.